Limitations of 16S rRNA Gene Sequencing to Characterize Lactobacillus Species in the Upper Genital Tract - O’Callaghan, Jessica L.; Willner, Dana; Buttini, Melissa; Huygens, Flavia; Pelzer, Elise S. (Frontiers in Cell and Developmental Biology, 2021)
The endometrial cavity is an upper genital tract site previously thought as sterile, however, advances in culture-independent, next-generation sequencing technology have revealed that this low-biomass site harbours a rich microbial community which includes multiple Lactobacillus species. These bacteria are considered to be the most abundant non-pathogenic genital tract commensals. Next-generation sequencing of the female lower genital tract has revealed significant variation amongst microbial community composition with respect to Lactobacillus sp. in samples collected from healthy women and women with urogenital conditions. The aim of this study was to evaluate our ability to characterize members of the genital tract microbial community to species-level taxonomy using variable regions of the 16S rRNA gene. Samples were interrogated for the presence of microbial DNA using next-generation sequencing technology that targets the V5–V8 regions of the 16S rRNA gene and compared to speciation using qPCR. In this analysis we explore next-generation sequencing of clinical genital tract isolates as a method for high throughput identification to species-level of key Lactobacillus sp. This technique is hindered by a lack of a consensus protocol and 16S rRNA gene region target allowing comparison between studies.